Analisis Strategi Online Consumer Relationship Management Pada Produk Pisau Cukur Banner - Admiral Budi Bramasta (Airlangga University, 2020)
This research uses a qualitative research approach with descriptive type and uses in-depth interviews as primary data in research data collection. This research is important because along with the digital transformation that is developing, marketing is now experiencing a development from transactional to marketing on a relationship basis. The use of various marketing tools to manage customer relationships such as Instagram and Whatsapp can also help to maintain customer relationships because this complete the customer's culture. The result of this research is an online CRM strategy built by Banner using artificial intelligence/chatbot to be able to manage relationships with customers. PT. AWP as the manager of the Banner product uses an online CRM program called Siska to be able to manage relations with customers